Two approaches to longitudinal qualitative analyses in rehabilitation and disability research. Issue 24 (19th November 2020) - Solomon, Patricia; Nixon, Stephanie; Bond, Virginia; Cameron, Cathy; Gervais, Nicole
Abstract: Purpose: Although relatively unknown within the field of rehabilitation, qualitative longitudinal research is ideal for rehabilitation and disability research that aims to understand health-related challenges over time. We describe the strengths and challenges of longitudinal qualitative research using two concrete examples. Materials and methods: Qualitative longitudinal research often involves in-depth interviews of participants on multiple occasions over time. Analytic approaches are complex, summarizing data both cross-sectionally and longitudinally. We present two detailed analytic approaches used in research with people living with HIV in Zambia and Canada. Results: Our experiences provide three recommendations. First, development of the initial analytic coding framework should include both inductive and deductive approaches. Second, given the large quantity of data generated through longitudinal qualitative research, it is important to proactively develop strategies for data analysis and management. Third, as retention of participants is challenging over time, we recommend the use of a consistent interviewer over the duration of the study to promote a trusting relationship. Conclusions: Longitudinal qualitative research has much to offer researchers and can provide clinicians with insights on the challenges of living with chronic and episodic disability. The flexibility in analytic approaches allows for diverse strategies to best address the rehabilitation and disability research questions and allow for insights into living with disability over time.